The Evolving Role of Product Manager - A Systematic Review - PARIKH Nishant (Foundations of Management, 2025)
This systematic review examines the evolving role of product manager (PM), from its inception in the early 20th century to its current state, with a focus on how technological advancements, shifting market dynamics, and evolving company’s strategy have shaped the profession. While numerous studies have explored the responsibilities of PMs, there has been little consolidation of these insights, leading to an unclear understanding of the role’s full scope. This review synthesizes the existing literature to clarify the key responsibilities of PMs in various contexts, including business-to-business (B2B) and business-to-consumer (B2C) environments, large enterprises (LEs) and small–medium enterprises (SMEs), Waterfall and Agile methodologies, and the unique challenges posed by artificial intelligence (AI)-driven products. By consolidating these insights, the paper provides a clearer understanding of the current state of product management and offers direction for future research to further define and enhance the role in an increasingly AI-centric world.